Foreleg Angle in Pig Carcasses as a Potential Indicator of Degree of Rigor Development and Meat Quality - Vasudevan, V. N.; Kutinarayanan, P.; Sathu, T.; Irshad, A.; Prajwal, S. (Journal of Meat Science, 2018)
The current study was conducted to assess the foreleg angle (FLA) in pig carcasses as a potential indicator of the degree of rigor development and correlate it with certain pork quality attributes. Sixteen cross-bred female Large White Yorkshire pigs (6-8 months, 90-100 kg) were humanely slaughtered and the FLA at 45 min post-slaughter for each carcass (held at about 35 oC) was determined by pictorial measurement. Meat samples were analysed for pH at 45 min post-slaughter (pHi), instrumental colour, drip loss, ultimate pH (pHu) and difference between pHi and pHu (ΔpH). FLA was significantly correlated (p<0.01) with pHi, ΔpH and chilling loss, while there was no significant correlation between pHu and L, a and b values. When observations were grouped based on the FLA (Group I: FLA>120° and Group II: FLA<120°), the mean FLA for Group I (11 Pigs) was 128.8° and that for Group II (5 Pigs) was 103°, with significantly different (p<0.05) pHi values of 6.17 and 5.82 respectively. The ΔpH values for the two groups were 0.4 and 0.13 respectively, which were significantly different, indicating greater degree of rigor development in the latter group. The chilling losses of the two groups were 5.82 and 7.70 per cent respectively which differed significantly. There was no significant difference in the L, a and b values between the two groups. The results of the study indicate that FLA of less than 120° is a potential indicator of rapid rigor development in pork carcasses, which is an indirect measure of the pre-slaughter stress and pork quality.